Changes in flood characteristics and the flood driving mechanism in the mountainous Haihe River Basin, China. Issue 16 (10th December 2019) - Feng, Ping; Wu, Jiezhao; Li, Jianzhu
ABSTRACT: Recently, the land surface in the Haihe River basin has changed, influencing the flood processes in the basin. To quantify this impact, seven typical sub-catchments were selected from different hydrological regions of the Haihe River basin for study. The non-parametric Mann-Kendall test was used to analyse for trends, and the non-parametric Pettitt test was adopted to detect any change point in the flood time series. Then, a hydrological model was established to simulate the effects of each potential driving factor on flood peak and volume. It was shown that flood peak and volume time series had decreased significantly, and the change point was around the year 1980. Groundwater depletion was not the main contribution to flood peak (FP) and volume (FV) decrease. In the Shifokou, Mubi and Lengkou sub-catchments, small hydraulic structures are the main driving factors for FP and FV decreasing. In the Xitaiyu, Daomaguan and Fuping sub-catchments, both land-use change and hydraulic structures are the main driving factors. The decreasing percentage decreases with the increase of the flood magnitude. The results provide valuable information for flood simulation and control in the Haihe River basin.